2018
DOI: 10.3389/fphys.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Patterns of Anoplophora chinensis (Forster) Chemosensory Receptor Genes from the Antennal Transcriptome

Abstract: The citrus long-horned beetle (CLB), Anoplophora chinensis (Forster) is a destructive native pest in China. Chemosensory receptors including odorant receptors (ORs), gustatory receptors (GRs), and ionotropic receptors (IRs) function to interface the insect with its chemical environment. In the current study, we assembled the antennal transcriptome of A. chinensis by next-generation sequencing. We assembled 44,938 unigenes from 64,787,784 clean reads and annotated their putative gene functions based on gene ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…In a recent study, 45 ORs were identified from the transcriptome of A. chinensis antennae. The qRT-PCR analysis showed that 41 ORs were highly expressed in the antennae; however, one OR was found to be highly expressed in the maxillary palp and the other three ORs were found to be highly expressed in the male body (Sun et al, 2018). Among the transcriptome of Adelphocoris lineolatus antennae with 57 randomly selected ORs, 26 ORs were found to be specifically expressed in male antennae, 16 ORs were found to be specifically expressed in female antennae, and the other ORs showed complex expression patterns, such as high expression in the body except the head or equal expression in male and female antennae (Xiao et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a recent study, 45 ORs were identified from the transcriptome of A. chinensis antennae. The qRT-PCR analysis showed that 41 ORs were highly expressed in the antennae; however, one OR was found to be highly expressed in the maxillary palp and the other three ORs were found to be highly expressed in the male body (Sun et al, 2018). Among the transcriptome of Adelphocoris lineolatus antennae with 57 randomly selected ORs, 26 ORs were found to be specifically expressed in male antennae, 16 ORs were found to be specifically expressed in female antennae, and the other ORs showed complex expression patterns, such as high expression in the body except the head or equal expression in male and female antennae (Xiao et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…The RNA samples were sent to Novogene Co., Ltd. (Beijing, China) for non-reference transcriptome sequencing. cDNA library construction and next-generation sequencing were performed as previously described ( Sun et al, 2018 ). In brief, RNA purity was checked using a NanoPhotometer spectrophotometer (IMPLEN, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuscript to be reviewed Holotrichia parallela and Anomala corpulenta, other agriculturally important scarab beetle pests (Ju et al, 2014;Yi et al, 2018). These numbers also resembled those obtained from the transcriptomes of other beetle species, such as Tomicus yunnanensis (Zhu, Zhao & Yang, 2012), Ips typographus, Dendroctonus ponderosae (Andersson et al, 2013), Tenebrio molitor (Liu et al, 2015), Brontispa longissima (Bin et al, 2017), Callosobruchus chinensis (Zhang et al, 2017) and Anoplophora chinensis (Sun et al, 2018). Furthermore, BUSCO completeness analysis showed that 98.7% conserved genes were found in this assembly, while the fraction of missing BUSCOs are quite low (1.3%).…”
Section: Discussionmentioning
confidence: 57%